Modelling Emergency Scenarios using Algebraic High Level Net Transformation Systems with Net Patterns - Trollmann, Frank; Kern, Maximilian; Albayrak, Sahin (Electronic Communications of the EASST, 2011)
Emergency operations are a good case study for dynamic systems. Theirsize and high dynamicity make modelling them a challenging task. Algebraic highlevel net transformation systems are a well suited technique for modelling such dynamicsystems. They consist of an algebraic high level net and a set of graph transformationrules. The net reflects the initial state of the operation and the transformationrules can be used to adapt this state to reflect the dynamicity of the operation.The applicability of graph transformation rules depends on the existence of a matchmorphism. While designing the algebraic high level net transformation system thedesigner has to ensure the existence of the right match morphisms for all reachableruntime states. This can be a tedious and error prone task for the designer. Thispaper uses a case study for modelling emergency operations with algebraic highlevel net transformation systems to show how the notion of net patterns can help thedesigner to cope with rule applicability.